2002
DOI: 10.1097/00005537-200203000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Amplification and p16(MTS1/CDK4I) Deletion Correlate With Poor Prognosis in Head and Neck Tumors

Abstract: We demonstrate that FISH is a simple and sensitive method for detecting cyclin D1 amplification and p16 deletion in head and neck cancer. Our results suggest that these two genetic aberrations together portend a poorer outcome than either of the abnormalities alone in head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
108
3
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 28 publications
8
108
3
8
Order By: Relevance
“…Several studies report that patients with HPV-positive head and neck tumours have an improved prognosis (Ritchie et al, 2003;Schlecht, 2005), whereas amplification of 11q13 has been associated with a more rapid and frequent recurrence of disease (Fujii et al, 2001) and poorer survival (Akervall et al, 1997;Rodrigo et al, 2000;Namazie et al, 2002). Weinberger et al (2006) has shown that patients with HPV-positive tumours which express high levels of p16 protein and low levels of p53 protein present with a favourable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that patients with HPV-positive head and neck tumours have an improved prognosis (Ritchie et al, 2003;Schlecht, 2005), whereas amplification of 11q13 has been associated with a more rapid and frequent recurrence of disease (Fujii et al, 2001) and poorer survival (Akervall et al, 1997;Rodrigo et al, 2000;Namazie et al, 2002). Weinberger et al (2006) has shown that patients with HPV-positive tumours which express high levels of p16 protein and low levels of p53 protein present with a favourable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 The second, p14(ARF), activates TP53 (tumor protein p53) through mediation of MDM2, an inhibitor of TP53, and CIP1(p21), an inhibitor of cyclin-dependent kinase CDK2, and results in cell cycle arrest at both G1 and G2/M. In 103 HNSCC tumors, Namazie et al 29 found CDKN2A deletions in 52% of cases and also observed that CYCLIN-D13CDK4 amplification had a significant correlation with recurrence, distant metastasis and survival. Bazan et al 11 reported that LOH at 9p21 and CDKN2A point mutations were associated with shorter survival in 64 cases of laryngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these differences (or other molecular differences not explored in our study) underlie prognosis in our patients remains unclear. Evidence for a prognostic effect of 11q13.3 amplification in HNSCC is inconsistent (Ruiz et al, 2012;Muller et al, 1997;Klussman et al, 2009;Hermsen et al, 2005;Rodrigo et al, 2000;Namazie et al, 2002;Ashman et al, 2003;Wreesmann et al, 2004;Xavier et al, 2012), but recent meta-analysis identified ANO1 (along with FADD) as the strongest potential host prognostic biomarkers across HNSCC (Reddy et al, 2016).…”
Section: Genes Chromosomes and Cancermentioning
confidence: 99%